The organizational implications of Brexit - Caterina Moschieri; Daniel J. Blake (Journal of Organization Design, 2019)
This point-of-view article examines the organizational implications of the UK's exit from the European Union (Brexit). We identify the effects of Brexit on firms' transaction costs in cross-border trade within Europe and highlight the importance of EU residency to secure licenses to operate. We also address how access to skilled labor may be affected by rising restrictions to immigration. Finally, we discuss the possible implications of Brexit for the organizational design of British firms and foreign firms operating in the UK.
Keywords: 650; Brexit; Multinational firms; Institutional changes; Organizational design